The Effectiveness of Deep Dialogue/Critical Thinking (DD/CT) Instruction on Scientific Reasoning Ability - Tampubolon, Erna Helena M; Sitepu, Christina (Jurnal Inovasi Pembelajaran Kimia, 2025)
Science inherently involves a process of reasoning, fostering honest, objective, critical, systematic, and creative attitudes, and shaping one's character and thought patterns to support informed conclusion-making. The Deep Dialogue/Critical Thinking (DD/CT) learning model is considered innovative as it encourages student activeness in the learning process by prompting them to seek knowledge and discover concepts, often leveraging technology to maximize interaction. This study investigated the impact of the DD/CT learning model on the mathematical reasoning ability of tenth-grade students at FKIP Universitas HKBP Nommensen. This research employed a quantitative approach, utilizing a quasi-experimental pretest-posttest control group design that involved both experimental and control classes. The research instruments underwent validity, reliability, discrimination, and difficulty testing, and the data met the prerequisites for normality and homogeneity. An independent t-test (α = 0.05) yielded a p-value of 0.004, indicating a statistically significant difference between the groups. Therefore, the DD/CT model has a positive effect on students’ mathematical reasoning skills.